Role of CYCLIN D1, E-Cadherin, EGFR, Her-2, KI67, and P53 Expressions as Prognostic Markers in Gall Bladder Cancer - Anshoo Agarwal, Rani Bansal, Mamta Gupta (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Worldwide gall bladder cancer (GBC) is known to be the commonest malignant tumour of the biliary tract .It is the most aggressive carcinoma of the biliary tract with short median survival from the time of diagnosis. The aggressive biologic behavior of the carcinoma and non-availability of sensitive screening tests for early detection may be responsible for the poor prognosis associated with GBC. Owing to the delayed diagnosis at an advanced stage, only 10% of the patients are found to be eligible for a curative surgical resection. Material and Methods: All consecutive patients diagnosed with neoplastic and non-neoplastic gallbladder lesions in the Department of Pathology, Subharti Medical College were included in the study between the year 2017 -2019. The hematoxylin and Eosin stained biopsies of 320 patients were assessed and out of them 100 patients were chosen as the sample for the study. The clinicopatholgical data of the 100 patients were compiled into a data base and de-identified. Results: Age distribution of Gall Bladder lesion cases in our study was from 30 years to more than 60 years of age. 46.20% of females in the age group of 45 years to 60 years presented with mass in the gall bladder. There was significant difference in the presence of mass between the Neoplastic and non-neoplastic group among 45-60 years of age (p<0.001). It was analyzed that there had been a significant difference between the neoplastic and non neoplastic tumour morphology and age distribution among males. The neoplastic tumours were highest in >60 years age group while neoplastic tumours were highest among 45-60 years age group . The presence of E-cadherin, Ki67 and P53 together suggested the presence of histological grade of carcinoma. There was no significant association between the presence of metastasis and biomarkers concentrations.The presence of E-cadherin, Ki67 and P53 together suggested the presence clinical stage of carcinoma . Conclusions: The minimal response of advanced cases of GBC to traditional treatments calls for new prognostic and treatment perspectives to be identified. Novel prognostic biomarkers could bring about the needed breakthrough in this regard as they will help in the identification of patients who will benefit tremendously from adjuvant and targeted therapies. Keywords: Cyclin D1, E-cadherin, EGFR, HER- 2, Ki67, p53 tumor marker ,neoplastic ,non -neoplastic Gall bladder lesions